Between two shores: crises of values and upbringing practices among Moroccan immigrant families in Andalusia, Spain. Issue 2 (4th March 2017) - Ruiz-Román, Cristóbal; Rascón, M. Teresa
Abstract : Moroccan and Spanish cultures have lived side by side in Andalusia for over five centuries, from the time of Al-Andalus. At the beginning of the twenty-first century, with the recent waves of migration brought on by globalisation, a new encounter is taking place in Andalusia between these two cultures from opposite shores of the Mediterranean. In this context, Moroccan families who have settled in Andalusia need to construct their personal identity within very different cultural scenarios from their own. This paper presents a qualitative analysis based on four case study families of Moroccan origin who have taken up residence in Andalusia. This multiple case study seeks to gain an insight into the upbringing practices and values used by parents. It also describes conflicts, expectations and strategies used by Moroccan adolescents, who participated in this study, in the constructing their identity in Andalusia.